1995
DOI: 10.1007/bf00176891
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous activity of pulmonary vagal receptors during high-frequency oscillation ventilation

Abstract: The purpose of the study was to examine the response of vagal pulmonary slowly adapting stretch receptors (SAR) to high-frequency oscillation ventilation (HFO) in rabbits by analyzing the afferent activity recorded in vagal single-fiber preparations. The vagal afferent activity was recorded during short runs of HFO with a stroke volume of 2-3 ml/kg applied at oscillation frequencies (fosc) of 5, 10, 15, 20, and 25 Hz and each frequency at three levels of mean airway pressure (P(aw)), namely, 1, 3, and 8 cm H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The rabbit is a species in which pulmonary afferents are well characterized (1,8,10,13,14). Afferent properties of SARs and RARs in the rabbit are essentially the same as those found in the cat (21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rabbit is a species in which pulmonary afferents are well characterized (1,8,10,13,14). Afferent properties of SARs and RARs in the rabbit are essentially the same as those found in the cat (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…1). Typically, SAR activity decreases as transpulmonary pressure decreases (8), such as during PEEP removal (22). In contrast, RARlike SARs are stimulated by PEEP removal, which is characteristic of RARs (17,21).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that P-and Ib cells display a phasic firing pattern that mimics SAR activity and tracks pulmonary oscillations [52,53]. This suggests that these neuronal populations act in some capacity to relay patterns of respiration from SARs in the lung to regions of the central nervous system (CNS) in which third order SAR neurons reside.…”
Section: Influence Of Respiratory Rhythm On Olfactory Neuronal Firingmentioning
confidence: 99%
“…Glick et al,6 using dogs placed on cardiopulmonary bypass, demonstrated that lung inflation to 20 em a ,o for 30 s caused a decrease in heart rate, systemic vascular resistance, and cardiac contractility that could be abolished by bilateral vagotomies. 14 In our patients, we hypothesize that as pulmonary compliance improved, regional hyperinflation occurred, leading to stimulation of the J receptors with subsequent bradycardia. 7 The natural stimulus for the J receptors appears to be pulmonary congestion; however, hyperinflation has also been shown to increase J receptor activity leading to apnea, hypotension, and bradycardia.…”
Section: Discussionmentioning
confidence: 68%